From hierarchical control to flexible interactive electricity services: A path to decarbonisation - Ilić, Marija D.; Carvalho, Pedro M.S. (Electric power systems research, 2022)
This paper first reviews today’s hierarchical control and highlights modelling and control assumptions which may no longer hold in the changing electric energy systems. To overcome this fundamental problem, we conceptualise electric energy systems as complex dynamical systems using physically intuitive multi-layered energy modelling as the basis for systematic diverse technology integration and control. Such modelling exhibits unique structure which comes from the conservation of instantaneous power (P) and the rate of change of instantaneous reactive power (Q̇). We name P and Q̇ as the rate of change of interaction variables (intVar) for characterising the interface of each system module with the rest of the system. The intVars are used as a means to model and control the interactive zoomed-out inter-modular (inter-area, inter-component) system dynamics. The control is distributed and modular as it utilises only a low-level detailed technology-specific model and intVar info exchange with the neighbours. As a result, the proposed approach can be used to support orderly and natural evolution from today’s hierarchical control to flexible interactive protocols for electricity services, key to implementing decarbonisation. •T&D system needs to be operated in a flexible data-enabled way in order to manage uncertainties in an efficient manner.•Efficient energy service requires temporal, spatial and functional alignment of energy resources and demand.•Models of interactions subject to conservation of instantaneous power and reactive power dynamics can be used to formulate optimization problems in the energy space as convex linear problems.